INVESTMENT RISKS OF CREDIT INSTITUTIONS - A. V. Russavskaya (Модернизация, инновация, развитие, 2016)
Development and implementation of investment projects are usually carried out under conditions of uncertainty determined by several factors. Eleven classification features are given for external risks divided into two groups: those that can be forecasted and those that can not. Investment risks areclassified according to the following main features: situation, scale, time to take decision, admissibility, specific aspects. Author’s risk management system structure is proposed.